Analisis Laporan Keuangan pada PT. Indofood Sukses Makmur Tbk Tahun 2020 dan 2021 - Yally Febrima Yossy; Asmy Febri Tama; Zulsantoni Zulsantoni (CV. Strata Persada Academia, 2023)
This study used a quantitative descriptive design. Research at PT. Indofood Sukses Makmur Tbk. December 2022 research. Researchers collected data via documentation. Horizontal analysis compares financial statements from multiple periods. The study's results are visible in PT.Indofood Sukses Makmur Tbk's liquidity ratio, which reflects the company's ability to satisfy short-term obligations: (1) the present ratio reveals 140% in 2020 and 130% in 2021. (2) 2020 and 2021 have 100% fast ratios. (3) 2020 cash ratio is 62%, 2021 73%. (1) The solvency ratio measures how much a company's assets are financed by debt. In 2020, it will be 51%, and in 2021, it will be 52%. (2) 2020 debt-to-equity ratio is 106%, 2021 107%. (1) The receivables turnover ratio was 15.4 times in 2020 and 15.9 times in 2021. (1) In 2020 and 2021, the net profit margin ratio was 11%. (2) 2020 and 2021 return on equity ratios are 11% and 13%.